Preparation method and application of water-free fiber

By introducing functional particles at high concentrations in the fibers to form a continuous raised structure, the existing water-free fabric has poor breathability and moisture permeability, and the water-free effect of maintaining the same gloss after being wet with water, and good breathability and water absorption.

CN119685964BActive Publication Date: 2025-05-02SHAOXING HUIQUN NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202510194603.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-05-02
Estimated Expiration
2045-02-21

AI Technical Summary

Technical Problem

The existing water-tree fabric has poor breathability and moisture permeability, which is not suitable for use in summer or sportswear, and the existing technology has insufficient content of nano-TiO2 added to the fibers, which makes it impossible to achieve the water-tree effect of the fabric.

Method used

Masterbatches are prepared by blending functional particles and PET, and fibers are obtained by melt spinning. The D50 particle size of functional particles is 70~340nm, the drafting ratio is 5~6, and the content of functional particles is 8~15wt%, so as to form a continuous convex structure to achieve a water traceless effect.

Benefits of technology

It achieves that the fabric has no significant change in gloss after being wet with water, has good breathability, high water absorption rate, short water droplet diffusion time, and high wicking height and drying rate, which significantly improves the water traceless effect of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685964B_ABST
    Figure CN119685964B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fabrics, and specifically relates to a preparation method and application of a water-free fiber, wherein the water-free fiber comprises a fiber matrix and functional particles, wherein the fiber matrix is PET, and the functional particles are nano-TiO2 with an organic coating layer on the surface, wherein the refractive index of the organic coating layer is 1.4-1.5, and the functional particles form a continuous convex structure on the fiber surface of the fiber matrix; the preparation method comprises: firstly blending and granulating the functional particles and PET to obtain a masterbatch, and then melt-spinning the masterbatch and PET to obtain a fiber, wherein the obtained fiber is the water-free fiber; wherein the drafting multiple in the melt-spinning process is 5-6; and the water-free fiber is used to prepare the water-free fabric. The water-free fabric prepared by the invention can achieve a good water-free effect, and at the same time has excellent moisture absorption and perspiration wicking performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fabrics, and particularly relates to a preparation method and application of water-free traceless fiber. Background Art

[0002] In the hot summer or when doing high-intensity exercise, the human body is particularly prone to sweating. However, the clothes people wear in the summer or during exercise are mostly light and thin. When the clothes are soaked with sweat, water marks appear on the surface of the clothes or even become transparent. This problem brings a lot of embarrassment to women in particular.

[0003] In order to solve this problem, people have developed water-free fabrics. The so-called water-free means that after water drips on the surface of the fabric / fabric, no trace of water drops can be seen on the surface of the fabric / fabric. For example, patent ZL202311386375.1 discloses a method for manufacturing a polypropylene composite fiber waterproof fabric. The fabric ensures the waterproof effect of the fabric by preventing water from penetrating. This fabric is obviously not suitable for making summer clothing, because the purpose of this waterproof fabric is to prevent external moisture from penetrating into the fabric. After sweating a lot in summer, the body's sweat cannot be discharged because the water cannot penetrate the fabric, and the comfort level is greatly reduced; there are also waterproof and breathable fabrics in the prior art. For example, Xinxing Jihua Materials Technology Research Institute Co., Ltd. reported the preparation and performance characterization of waterproof and breathable membrane composite fabrics. The waterproof and breathable fabrics were obtained by combining polyester fabric grey cloth with PU waterproof membrane, and its breathability can reach 6000g·m -2 ·d -1 , which is equivalent to 250g of moisture permeability per hour, while people sweat 1.5~3L per hour during exercise. In contrast, the moisture permeability of the waterproof and breathable membrane composite fabric is far from enough. The above-mentioned fabrics that can achieve water-free are mostly waterproof fabrics / fabrics, but this type of fabric has poor air permeability and moisture permeability and is not suitable for making summer clothing or sportswear. There is no report on ordinary fabrics achieving water-free.

[0004] In the prior art, nano-TiO2 is mostly used in the field of anti-penetration. Inspired by this technology, people try to achieve anti-penetration by adding nano-TiO2 to the fiber, and then achieve the water-free effect of the fabric. For example, patent application CN115044998A obtains anti-penetration fiber by melt spinning anti-penetration functional masterbatch and resin matrix, wherein the addition amount of masterbatch is 10~20%, and the content of TiO2 in the masterbatch is 10~20%, so the actual content of titanium dioxide in the fiber is only 1~4%; patent application CN117261377A introduces nano-TiO2 on the fiber surface by impregnation, and the concentration of TiO2 in the dipping solution is less than 1%; these two methods cannot form a continuous convex structure on the fiber surface, and cannot achieve the water-free effect of the fabric; in the anti-penetration fiber prepared by patent CN213624546U, the content of nano-TiO2 in the local area of ​​the coating layer can reach 17~20%, but The content of nano-TiO2 in the entire fiber is still very low, and a resin layer is also coated on the outside of its functional layer. The fiber obtained in this way can play a certain role in anti-see-through, but it cannot achieve the effect of no water marks; Patent application CN113699610A involves a high light-resistant anti-see-through fiber, which is a skin-core structure, and the content of nano-TiO2 in the entire fiber is 2~20%, of which nano-TiO2 is mainly concentrated in the cortex, accounting for 70% of the total amount. With such a high content of inorganic particles, the mechanical strength of the cortex must be low, and it cannot have a high draft multiple. Therefore, the surface of its fiber cannot form a continuous convex structure. This fiber has a good anti-see-through effect but no good effect on water marks. Although the above patents have undergone various attempts, due to defects in the method, the fabrics made of these anti-see-through fibers have never been able to achieve a good water-free effect.

[0005] Therefore, it is urgent to develop a new method for preparing water-free fabrics to solve the above problems. Summary of the invention

[0006] The purpose of the invention is to solve the problems existing in the prior art and provide a preparation method and application of water-free fiber.

[0007] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing water-free traceless fiber comprises the following steps: firstly, functional particles and PET are blended and granulated to obtain master batches, and then the master batches and PET are melt-spun to obtain fibers, wherein the obtained fibers are water-free traceless fibers; wherein the D50 particle size (i.e., median diameter or median particle size) of the functional particles is 70-340 nm, the drafting multiple in the melt spinning process is 5-6, and the content of the functional particles in the water-free traceless fibers is 8-15 wt %, so that the functional particles can form a continuous convex structure on the fiber surface of a fiber matrix; the water-free traceless fiber comprises a fiber matrix and functional particles; the fiber matrix is ​​PET; the functional particles are nano-TiO2 with an organic coating layer on the surface, and the refractive index of the organic coating layer is 1.4-1.5; and the functional particles form a continuous convex structure on the fiber surface of the fiber matrix.

[0009] As the preferred technical solution:

[0010] In the method for preparing the water-free fiber as described above, the steps for preparing the functional particles are as follows:

[0011] (a) Physical coating modification of nano-TiO2 using silane coupling agent;

[0012] (b) adding MMA (methyl methacrylate) and an initiator into a reactor to react to obtain an MMA prepolymer, then adding a catalyst, a chain transfer agent and the product of step (a) into the reactor to continue the reaction, then adding HTEMPO (4-hydroxy-2,2,6,6-tetramethoxypiperidine, CAS: 2403-88-5) into the reactor to continue the reaction, and after the reaction is completed, removing the small molecules in vacuo (i.e., reducing the pressure in the reactor to below 80 Pa and maintaining it for 10 to 15 minutes at 160 to 190° C.), and cooling the discharged material;

[0013] (c) The product of step (b) is crushed (pre-crushed, air flow crushed) to obtain functional particles.

[0014] For melt spinning technology, the amount of nano-TiO2 added to the fiber prepared by the prior art cannot reach the level of the present invention (8-15wt%), and the amount of TiO2 added in the prior art, such as the full matte product, is no more than 2.5wt%. TiO2 is an inorganic functional particle, which is prone to phase separation when added in large quantities in the resin matrix, resulting in a sharp deterioration in the mechanical strength of the material, and cannot meet the processing requirements, so it is difficult to achieve a high content of inorganic functional particles in the fiber. The present invention prepares a functional particle that can be added in large quantities to the fiber.

[0015] In the method for preparing a water-free fiber as described above, the silane coupling agent is one or more of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and vinyltriethoxysilane;

[0016] The initiator is dibenzoyl peroxide, the chain transfer agent is dodecyl mercaptan, and the catalyst is AlCl3;

[0017] The mass ratio of silane coupling agent, nano-TiO2, MMA, initiator, chain transfer agent, catalyst and HTEMPO is 1~3:60~70:25~35:0.01~0.05:0.5~1:0.01~0.05:1~4.

[0018] The method for preparing a water-free fiber as described above, the specific process of step (a) is: adding a silane coupling agent and nano-TiO2 into a high-speed mixer, controlling the speed to 2500-3000 r / min, the temperature to 70-80°C, and stirring for 2-3 hours;

[0019] In step (b), the temperature of the first reaction is 40-60°C, the pressure is 0.1-0.2 MPa, the time is 1-2 h, and the speed is 100-150 r / min; the temperature of the second reaction is 60-90°C, the pressure is 0.2-0.4 MPa, and the time is 1-2 h; the temperature and pressure of the third reaction are the same as those of the second reaction, and the time is 0.5-1 h.

[0020] In the method for preparing water-free traceless fiber as described above, the content of functional particles in the masterbatch is 50-60wt%.

[0021] In the preparation method of a water-free fiber as described above, the process parameters of melt spinning include: the temperature of the screw extruder is 280~285°C in zone one, 285~290°C in zone two, 285~290°C in zone three, 295~300°C in zone four, and 290~295°C in zone five; three pairs of drafting rollers are used in the melt spinning process, the temperature of the first pair of drafting rollers is 110~115°C, and the rotation speed is 600~650m / min, the temperature of the second pair of drafting rollers is 125~130°C, and the rotation speed is 2400~2600m / min, and the temperature of the third pair of rollers is 210~220°C, and the rotation speed is 3000~3600m / min.

[0022] In the method for preparing a water-free fiber as described above, the organic coating layer is PMMA with a number average molecular weight of 2000-3000 g / mol and a thickness of 10-20 nm.

[0023] A method for preparing a water-free mark fiber as described in any of the above items, wherein the specification of the water-free mark fiber is 20~300D / 24~576F, and the tensile breaking strength is 5.88~6.25cN / dtex.

[0024] A water-free mark fabric is woven from water-free mark fibers, wherein the water-free mark fibers are prepared by the preparation method of the water-free mark fibers as described in any one of the above items.

[0025] As the preferred technical solution:

[0026] The water-free fabric as described above is a knitted fabric, the needle count of the circular knitting machine is 40G, and the gram weight is 150~300g / m 2 Or, the water-free fabric is a plain fabric with a warp density of 120-130 strands / 10cm, a weft density of 130-150 strands / 10cm, and a gram weight of 40-300g / m 2 Or, the water-free fabric is a twill fabric with a warp density of 120~190 strands / 10cm, a weft density of 120~150 strands / 10cm, and a gram weight of 40~300g / m 2 ;

[0027] The percentage of the glossiness of the water-free fabric when the moisture content is 100wt% to the glossiness when the moisture content is 0wt% is 95-100%, and this percentage is close to 100%, indicating that the glossiness of the water-free fabric does not change significantly before and after wetting, and the water-free effect is obvious;

[0028] The air permeability of water-free fabric is 18~23mm / s;

[0029] The water absorption rate of the water-free fabric is ≥152%, the water droplet diffusion time is ≤1.9s, the wicking height is ≥112mm, and the drying rate is ≥0.46g / h.

[0030] Principle of the invention:

[0031] The reason why human eyes can see objects is because of the reflection of light on the surface of the object. For rough surfaces such as fabrics, diffuse reflection is usually the main method. The diffuse reflection light on the surface of the object enters the human eye so that we can observe the object. For monochrome fabrics, the diffuse reflection ability of each area of ​​the fabric under natural light is the same, so the color of the entire area of ​​the fabric is uniform and consistent. If water drops are dropped onto the surface of the fabric, we can observe that the water drops form obvious watermarks on the surface of the fabric. The reason is that the water drops form a thin layer of water film on the surface of the fabric, which covers the surface of the fabric fiber, making the originally rough fiber surface smooth. At this time, the diffuse reflection ability of the object surface to light is weakened, and the mirror reflection ability is enhanced. Most angles of light cannot be received by the human eye after mirror reflection, which reduces the light entering the human eye in the area wetted by water. Therefore, the color of the area wetted by water is observed to be darker than that of the unwetted area, thus showing water marks on the surface of the fabric.

[0032] The fiber of the present invention contains a high concentration of functional particles, a large number of which are distributed on the surface and inside of the fiber. The surface of the fiber is rough with many protrusions, and a large number of irregular grooves are formed between the functional particles on the surface. These grooves can fully play the role of water guidance, which is conducive to the rapid spreading of water droplets on the fiber surface, so that water can remain in the grooves on the fiber surface in a thinner water layer, and combined with the optical properties of the water-free fiber, water-free can be achieved.

[0033] like Figure 1 As shown, Figure 1 In the figure, the left picture is a schematic diagram of the water-free fiber, and the right picture is a cross-sectional view of the fiber. Water remains in the grooves formed by the functional particle protrusions on the fiber surface. At this time, due to the presence of water, in addition to diffuse reflection, mirror reflection will also occur on the fiber surface. The larger the mirror reflection area, the weaker the diffuse reflection light intensity. Due to the special morphology of the fiber surface, water only remains in the surface grooves. Therefore, diffuse reflection is still the main feature in most areas of the fiber surface, and mirror reflection only occurs in the grooves where water remains on the fiber surface. Mirror reflection at the grooves can be divided into two cases, such as Figure 1 In A and B, the maximum incident light angle of A is relatively large. At this time, the light will be refracted and reflected by the mirror on the water surface of the groove, and the mirror reflected light will hit the adjacent protruding particles. The light will be re-propagated on the surface of the particle in the form of diffuse reflection light, and the refracted light is similar to B. The incident light angle in B is very small. According to the Fresnel phenomenon, the smaller the incident light angle, the lower the proportion of reflected light. At this time, the light is mainly transmitted, and the reflected light is extremely weak and can be ignored. When light enters water from air, the refractive index of water (n 水 =1.33) is greater than the refractive index of air (n 空气 =1), when light enters the optically dense medium from the optically sparse medium, the angle between the light and the normal is further reduced, and it will be refracted twice at the interface between water and fiber (the base material of the fiber is PET, and the refractive index of PET is about 1.55, which is greater than the refractive index of water). At this time, the light refracted by the air / water interface is refracted twice at the water / PET interface as the incident light. At this time, the angle of the refracted light is approximately equal to 0 degrees. At this time, the light is transmitted through the coating layer of the functional particles as the incident light, and the light hits the nano-TiO2 particles, and emits diffuse reflection on the surface of the nano-TiO2 particles. The diffusely reflected light passes through the coating layer of the functional particles again and enters PET. Since the refractive index of the coating layer of the functional particles is 1.4~1.5, which is less than PET, the angle of the light is reduced after the light is refracted by the interface, and most of the light can return to the fiber surface. In this way, the light intensity entering the human eye after the superposition of diffuse reflection, refraction and reflection in the part wetted by water basically does not change. Therefore, even if the fabric / fabric is wetted by water, no water mark is shown on the fabric / fabric, thereby achieving water-free on conventional fabrics.

[0034] For ordinary fibers, a layer of water film is formed on the fiber surface after absorbing water, and the specular reflection of light on the fiber surface is enhanced. Most of the light cannot enter the human eye due to specular reflection; at the same time, due to the absence of functional particles, part of the light is refracted on the fiber surface and passes through the fiber, further reducing the intensity of light that can be diffusely reflected to the human eye. Therefore, under this dual effect, it can be clearly observed that the color of the part of the fiber / fabric that is wetted by water becomes darker, thus showing water marks.

[0035] Beneficial effects:

[0036] The present invention greatly reduces the transmission effect of light on the surface of fabrics / textiles by introducing functional particles at high concentrations into the fibers. The wetted area of ​​the fabric / textile retains the same reflection effect as the unwetted area, so that the light intensity reflected to the human eye from the wetted area and the unwetted area remains consistent, so that the fabric / textile will not produce color difference on the surface after being wetted, achieving a water-free effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The present invention is a schematic diagram of the water-free fiber and the principle of achieving water-free. DETAILED DESCRIPTION

[0038] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0039] The test methods of relevant indicators in the embodiments and comparative examples are as follows:

[0040] Glossiness of fabric: Tested according to the reference standard FZT 01097-2006 "Fabric Gloss Test Method";

[0041] Fabric air permeability: Tested according to GB / T 5453-1997 "Determination of air permeability of textile fabrics";

[0042] Water absorption rate, water droplet diffusion time, wicking height and drying rate of fabrics: obtained by testing with reference to standard GB / T 21655.1-2023 "Evaluation of the quick-drying property of textiles Part 1: Single combination test method";

[0043] Fiber tensile breaking strength: measured in accordance with GB / T 14344-2008 "Test method for tensile properties of chemical filaments";

[0044] Thickness of the organic coating layer: The sample to be tested was prepared into a dispersion with a concentration of 1.0 mg / mL using anhydrous ethanol. A proper amount of the dispersion was taken with a pipette and dropped onto the ultra-thin copper mesh. After the ethanol evaporated, a JEM-2100F transmission electron microscope was used for analysis and testing.

[0045] Refractive index of organic coating layer: obtained by testing with reference to standard GB / T 6691-2007 “Determination of refractive index of resin finishing agents”.

[0046] Example 1

[0047] A method for preparing water-free fiber, the specific steps are as follows:

[0048] (1) Raw material preparation:

[0049] PET: The manufacturer is Yizheng Chemical Fiber, the brand is FC510A;

[0050] Nano-TiO2;

[0051] Silane coupling agent: γ-(2,3-epoxypropoxy)propyltrimethoxysilane;

[0052] Catalyst: AlCl3;

[0053] MMA;

[0054] Initiator: dibenzoyl peroxide;

[0055] Chain transfer agent: dodecyl mercaptan;

[0056] HTEMPO (4-hydroxy-2,2,6,6-tetramethoxypiperidine, CAS: 2403-88-5);

[0057] (2) Preparation of functional particles:

[0058] (2.1) Add silane coupling agent and nano-TiO2 into a high-speed mixer, control the speed to 2500r / min, the temperature to 70℃, and stir for 2h;

[0059] (2.2) Add MMA and initiator to the reactor to react to obtain MMA prepolymer, then continue to add catalyst, chain transfer agent and the product of step (2.1) to the reactor to continue the reaction, then continue to add HTEMPO to the reactor to continue the reaction, after the reaction is completed, remove the small molecules in vacuo (i.e., at 180°C, reduce the pressure in the reactor to 70 Pa and maintain it for 13 minutes), and cool the discharged material;

[0060] Wherein, in steps (2.1) to (2.2), the mass ratio of silane coupling agent, nano-TiO2, MMA, initiator, chain transfer agent, catalyst, and HTEMPO is 2:68:26:0.01:0.5:0.02:3.47; in step (2.2), the temperature of the first reaction is 45°C, the pressure is 0.1MPa, the time is 1h, and the speed is 100r / min; the temperature of the second reaction is 75°C, the pressure is 0.3MPa, and the time is 1.5h; the temperature and pressure of the third reaction are the same as those of the second reaction, and the time is 0.5h;

[0061] (2.3) crushing the product of step (2.2) (pre-crushing, airflow crushing) to obtain functional particles with a D50 particle size of 70 nm;

[0062] (3) Preparation of water-free fibers:

[0063] (3.1) Blending the functional particles and PET to obtain a masterbatch;

[0064] Among them, the content of functional particles in the masterbatch is 55wt%;

[0065] (3.2) The masterbatch and PET are melt-spun to obtain fibers, and the obtained fibers are water-free fibers;

[0066] The process parameters of melt spinning include: the temperature of the screw extruder is 280°C for zone 1, 285°C for zone 2, 288°C for zone 3, 290°C for zone 4, and 290°C for zone 5; three pairs of drafting rollers are used in the melt spinning process, the temperature of the first pair of drafting rollers is 110°C and the rotation speed is 600m / min, the temperature of the second pair of drafting rollers is 125°C and the rotation speed is 2400m / min, and the temperature of the third pair of rollers is 210°C and the rotation speed is 3000m / min.

[0067] The final water-free fiber includes functional particles and a PET fiber matrix with a specification of 20D / 24F and a tensile breaking strength of 5.96 cN / dtex. The content of functional particles in the fiber is 10wt%. The functional particles are nano-TiO2 with an organic coating layer with a thickness of 10nm and a refractive index of 1.42 on the surface. The organic coating layer is PMMA with a number average molecular weight of 2500g / mol. The functional particles form a continuous convex structure on the surface of the fiber matrix.

[0068] A water-free fabric made of the water-free fiber is a knitted fabric with a circular knitting machine needle count of 40G and a gram weight of 150g / m 2 ;

[0069] The glossiness of the water-free fabric when the moisture content is 100wt% is 95.8% of the glossiness when the moisture content is 0wt%; the air permeability of the water-free fabric is 21mm / s; the water absorption rate of the water-free fabric is 159%, the water droplet diffusion time is 1.5s, the wicking height is 118mm, and the drying rate is 0.52g / h.

[0070] Comparative Example 1

[0071] A method for preparing a fiber, which is the same as that of Example 1, except that in step (3.2), the rotation speed of the first pair of drafting rollers is 600 m / min, the rotation speed of the second pair of drafting rollers is 1600 m / min, and the rotation speed of the third pair of drafting rollers is 2400 m / min.

[0072] The final fiber had a tensile breaking strength of 3.97 cN / dtex, and the functional particles did not form a protruding structure on the fiber surface of the fiber matrix.

[0073] A fabric made of the fiber of this comparative example, the weaving specification of the fabric is the same as that of Example 1;

[0074] The glossiness of the fabric when the moisture content is 100wt% is 88% of the glossiness when the moisture content is 0wt%, the air permeability of the fabric is 18mm / s, the water absorption rate of the fabric is 108%, the water droplet diffusion time is 4.8s, the wicking height is 64mm, and the drying rate is 0.21g / h.

[0075] Compared with Example 1, the glossiness percentage of Comparative Example 1 is weakened, and the moisture conduction and dehumidification ability of the fabric is also significantly deteriorated; this is because in Comparative Example 1, the fiber is not fully stretched and a rough structure with raised surfaces cannot be formed. The lack of this structure reduces the effective area of ​​light on the particle surface, thereby worsening the diffusion effect of the fiber surface and reducing the glossiness percentage of the fiber after wetting; at the same time, since no raised rough surface structure is formed, the fiber does not have a strong capillary effect, which causes the moisture conduction and dehumidification ability of the fabric to be significantly deteriorated.

[0076] Example 2

[0077] A method for preparing water-free fiber, the specific steps are as follows:

[0078] (1) Raw material preparation:

[0079] PET: The manufacturer is Yizheng Chemical Fiber, brand number is TFW100;

[0080] Nano-TiO2;

[0081] Silane coupling agent: γ-methacryloxypropyltrimethoxysilane;

[0082] Catalyst: AlCl3;

[0083] MMA;

[0084] Initiator: dibenzoyl peroxide;

[0085] Chain transfer agent: dodecyl mercaptan;

[0086] HTEMPO (4-hydroxy-2,2,6,6-tetramethoxypiperidine, CAS: 2403-88-5);

[0087] (2) Preparation of functional particles:

[0088] (2.1) Add silane coupling agent and nano-TiO2 into a high-speed mixer, control the speed to 2800r / min, the temperature to 75℃, and stir for 3h;

[0089] (2.2) Add MMA and initiator to the reactor to react to obtain MMA prepolymer, then continue to add catalyst, chain transfer agent and the product of step (2.1) to the reactor to continue the reaction, then continue to add HTEMPO to the reactor to continue the reaction, after the reaction is completed, remove the small molecules in vacuo (i.e., at 160°C, reduce the pressure in the reactor to 65 Pa and maintain for 10 minutes), and cool the discharged material;

[0090] Wherein, in steps (2.1) to (2.2), the mass ratio of silane coupling agent, nano-TiO2, MMA, initiator, chain transfer agent, catalyst, and HTEMPO is 1:70:25:0.02:0.8:0.03:3.15; in step (2.2), the temperature of the first reaction is 40°C, the pressure is 0.1MPa, the time is 1h, and the speed is 120r / min; the temperature of the second reaction is 60°C, the pressure is 0.2MPa, and the time is 1.5h; the temperature and pressure of the third reaction are the same as those of the second reaction, and the time is 0.5h;

[0091] (2.3) crushing the product of step (2.2) (pre-crushing, airflow crushing) to obtain functional particles with a D50 particle size of 120 nm;

[0092] (3) Preparation of water-free fibers:

[0093] (3.1) Blending the functional particles and PET to obtain a masterbatch;

[0094] Among them, the content of functional particles in the masterbatch is 52wt%;

[0095] (3.2) The masterbatch and PET are melt-spun to obtain fibers, and the obtained fibers are water-free fibers;

[0096] The process parameters of melt spinning include: the temperature of the screw extruder is 285°C for zone 1, 290°C for zone 2, 290°C for zone 3, 295°C for zone 4, and 295°C for zone 5; three pairs of drafting rollers are used in the melt spinning process, the temperature of the first pair of drafting rollers is 110°C and the rotation speed is 620m / min, the temperature of the second pair of drafting rollers is 128°C and the rotation speed is 2450m / min, and the temperature of the third pair of rollers is 220°C and the rotation speed is 3400m / min.

[0097] The final water-free fiber includes functional particles and a PET fiber matrix, with a specification of 75D / 72F and a tensile breaking strength of 6.22 cN / dtex. The content of functional particles in the fiber is 8wt%. The functional particles are nano-TiO2 with an organic coating layer with a thickness of 12 nm and a refractive index of 1.48 on the surface, and the organic coating layer is PMMA with a number average molecular weight of 2200 g / mol. The functional particles form a continuous convex structure on the surface of the fiber matrix.

[0098] A water-free fabric made of the water-free fiber is a knitted fabric with a circular knitting machine needle count of 40G and a gram weight of 300g / m 2 ;

[0099] The glossiness of the water-free fabric when the moisture content is 100wt% is 97.4% of the glossiness when the moisture content is 0wt%; the air permeability of the water-free fabric is 20mm / s; the water absorption rate of the water-free fabric is 155%, the water droplet diffusion time is 1.8s, the wicking height is 115mm, and the drying rate is 0.48g / h.

[0100] Comparative Example 2

[0101] A method for preparing fibers is basically the same as that of Example 2, except that in step (2.2) of this comparative example, a mixture of the same mass (MMA and styrene in a mass ratio of 1:1) is used to replace the MMA in the original Example 2 to obtain functional particles coated with MMA-styrene copolymer.

[0102] In the finally obtained fiber, the refractive index of the organic coating layer on the surface of the functional particles is 1.58.

[0103] A fabric made of the fiber of this comparative example, the weaving specification of the fabric is the same as that of Example 2;

[0104] The glossiness of the fabric when the moisture content is 100wt% accounts for 83% of the glossiness when the moisture content is 0wt%.

[0105] Compared with Example 2, the gloss percentage of the fabric in Example 2 is significantly reduced. This is because the refractive index of the coating layer on the surface of the functional particles in Example 2 is relatively large and greater than the refractive index of the polyester matrix. After the light is diffusely reflected on the surface of the inorganic particles, the light will be refracted again at the interface between the coating layer and the polyester matrix. Since the light enters the polyester matrix layer with a lower refractive index from the coating layer with a higher refractive index (i.e., from the optically dense medium to the optically sparse medium), the refraction angle after refraction will increase, which causes more light to propagate into the fiber, and less light returns to the fiber surface; therefore, less light enters the human eye, which is manifested as a decrease in the gloss percentage of the fabric. On the fabric, due to the difference in gloss, the color difference can be clearly observed between the wetted part and the non-wetted part, thereby showing water marks.

[0106] Example 3

[0107] A method for preparing water-free fiber, the specific steps are as follows:

[0108] (1) Raw material preparation:

[0109] PET: The manufacturer is Yizheng Chemical Fiber, the brand is SD-A;

[0110] Nano-TiO2;

[0111] Silane coupling agent: vinyl triethoxysilane;

[0112] Catalyst: AlCl3;

[0113] MMA;

[0114] Initiator: dibenzoyl peroxide;

[0115] Chain transfer agent: dodecyl mercaptan;

[0116] HTEMPO (4-hydroxy-2,2,6,6-tetramethoxypiperidine, CAS: 2403-88-5);

[0117] (2) Preparation of functional particles:

[0118] (2.1) Add silane coupling agent and nano-TiO2 into a high-speed mixer, control the speed to 2500r / min, the temperature to 78℃, and stir for 2.2h;

[0119] (2.2) Add MMA and initiator to the reactor to react to obtain MMA prepolymer, then continue to add catalyst, chain transfer agent and the product of step (2.1) to the reactor to continue the reaction, then continue to add HTEMPO to the reactor to continue the reaction, after the reaction is completed, remove the small molecules in vacuo (i.e., at 175°C, reduce the pressure in the reactor to 73 Pa and maintain for 12 minutes), and cool the discharged material;

[0120] Wherein, in steps (2.1) to (2.2), the mass ratio of silane coupling agent, nano-TiO2, MMA, initiator, chain transfer agent, catalyst, and HTEMPO is 3:65:30:0.05:0.5:0.01:1.44; in step (2.2), the temperature of the first reaction is 50°C, the pressure is 0.2MPa, the time is 2h, and the speed is 120r / min; the temperature of the second reaction is 85°C, the pressure is 0.25MPa, and the time is 1h; the temperature and pressure of the third reaction are the same as those of the second reaction, and the time is 0.5h;

[0121] (2.3) crushing the product of step (2.2) (pre-crushing, airflow crushing) to obtain functional particles with a D50 particle size of 220 nm;

[0122] (3) Preparation of water-free fibers:

[0123] (3.1) Blending the functional particles and PET to obtain a masterbatch;

[0124] Among them, the content of functional particles in the masterbatch is 50wt%;

[0125] (3.2) The masterbatch and PET are melt-spun to obtain fibers, and the obtained fibers are water-free fibers;

[0126] The process parameters of melt spinning include: the temperature of the screw extruder is 285°C in zone 1, 290°C in zone 2, 290°C in zone 3, 300°C in zone 4, and 295°C in zone 5; three pairs of drafting rollers are used in the melt spinning process, the temperature of the first pair of drafting rollers is 112°C and the rotation speed is 650m / min, the temperature of the second pair of drafting rollers is 130°C and the rotation speed is 2500m / min, and the temperature of the third pair of rollers is 220°C and the rotation speed is 3300m / min.

[0127] The final water-free fiber includes functional particles and a PET fiber matrix, with a specification of 300D / 576F and a tensile breaking strength of 6.25cN / dtex. The content of functional particles in the fiber is 8wt%. The functional particles are nano-TiO2 with an organic coating layer with a thickness of 15nm and a refractive index of 1.45 on the surface, and the organic coating layer is PMMA with a number average molecular weight of 2000g / mol. The functional particles form a continuous convex structure on the surface of the fiber matrix.

[0128] A water-free fabric made of the water-free fiber is a plain fabric with a warp density of 120 strands / 10cm, a weft density of 130 strands / 10cm, and a gram weight of 40g / m 2 ;

[0129] The glossiness of the water-free fabric when the moisture content is 100wt% is 96.3% of the glossiness when the moisture content is 0wt%; the air permeability of the water-free fabric is 23mm / s; the water absorption rate of the water-free fabric is 156%, the water droplet diffusion time is 1.7s, the wicking height is 115mm, and the drying rate is 0.46g / h.

[0130] Comparative Example 3

[0131] A method for preparing a fiber is the same as that of Example 3, except that the content of the functional particles in the fiber finally obtained in this comparative example is 6 wt %.

[0132] The final fiber has a tensile breaking strength of 6.27 cN / dtex.

[0133] A fabric made of the fiber of this comparative example, the weaving specification of the fabric is the same as that of Example 3;

[0134] The glossiness of the fabric when the moisture content is 100wt% is 89% of the glossiness when the moisture content is 0wt%, the air permeability of the fabric is 18mm / s, the water absorption rate of the fabric is 114%, the water droplet diffusion time is 4.5s, the wicking height is 72mm, and the drying rate is 0.23g / h.

[0135] Compared with Example 3, the glossiness percentage of Comparative Example 3 is weakened, and the moisture conduction and dehumidification ability of the fabric is also obviously inferior to that of Example 3. The reason for this difference is that the filling amount of the functional particles in the fiber is insufficient. Due to the insufficient filling amount, the fiber cannot form a rough structure with raised surface during the stretching process, which leads to a reduction in the effective area of ​​light on the particle surface, thereby worsening the diffusion effect of the fiber surface, and ultimately reducing the glossiness percentage of the fabric after being wetted; at the same time, since no raised rough surface structure is formed, these fibers lack a strong capillary effect, and therefore do not have high moisture conduction and dehumidification capabilities, which ultimately leads to poor moisture absorption and dehumidification effects of the fabric.

[0136] Example 4

[0137] A method for preparing water-free fiber, the specific steps are as follows:

[0138] (1) Raw material preparation:

[0139] PET: The manufacturer is Yizheng Chemical Fiber, brand number is FG600;

[0140] Nano-TiO2;

[0141] Silane coupling agent: γ-(2,3-epoxypropoxy)propyltrimethoxysilane;

[0142] Catalyst: AlCl3;

[0143] MMA;

[0144] Initiator: dibenzoyl peroxide;

[0145] Chain transfer agent: dodecyl mercaptan;

[0146] HTEMPO (4-hydroxy-2,2,6,6-tetramethoxypiperidine, CAS: 2403-88-5);

[0147] (2) Preparation of functional particles:

[0148] (2.1) Add silane coupling agent and nano-TiO2 into a high-speed mixer, control the speed to 3000r / min, the temperature to 73℃, and stir for 2.5h;

[0149] (2.2) Add MMA and initiator to the reactor to react to obtain MMA prepolymer, then continue to add catalyst, chain transfer agent and the product of step (2.1) to the reactor to continue the reaction, then continue to add HTEMPO to the reactor to continue the reaction, after the reaction is completed, remove the small molecules in vacuo (i.e., at 180°C, reduce the pressure in the reactor to 77 Pa and maintain it for 14 minutes), and cool the discharged material;

[0150] Wherein, in steps (2.1) to (2.2), the mass ratio of silane coupling agent, nano-TiO2, MMA, initiator, chain transfer agent, catalyst, and HTEMPO is 1.9:60:33:0.05:1:0.05:4; in step (2.2), the temperature of the first reaction is 60°C, the pressure is 0.2MPa, the time is 1.5h, and the speed is 150r / min; the temperature of the second reaction is 90°C, the pressure is 0.4MPa, and the time is 2h; the temperature and pressure of the third reaction are the same as those of the second reaction, and the time is 0.8h;

[0151] (2.3) crushing the product of step (2.2) (pre-crushing, airflow crushing) to obtain functional particles with a D50 particle size of 200 nm;

[0152] (3) Preparation of water-free fibers:

[0153] (3.1) Blending the functional particles and PET to obtain a masterbatch;

[0154] Among them, the content of functional particles in the masterbatch is 60wt%;

[0155] (3.2) The masterbatch and PET are melt-spun to obtain fibers, and the obtained fibers are water-free fibers;

[0156] The process parameters of melt spinning include: the temperature of the screw extruder is 283°C in zone 1, 287°C in zone 2, 290°C in zone 3, 300°C in zone 4, and 295°C in zone 5; three pairs of drafting rollers are used in the melt spinning process, the temperature of the first pair of drafting rollers is 115°C and the rotation speed is 600m / min, the temperature of the second pair of drafting rollers is 130°C and the rotation speed is 2600m / min, and the temperature of the third pair of rollers is 215°C and the rotation speed is 3600m / min.

[0157] The final water-free fiber includes functional particles and a PET fiber matrix, with a specification of 200D / 288F and a tensile breaking strength of 6.17 cN / dtex. The content of functional particles in the fiber is 8wt%. The functional particles are nano-TiO2 with an organic coating layer with a thickness of 20 nm and a refractive index of 1.5 on the surface. The organic coating layer is PMMA with a number average molecular weight of 2800 g / mol. The functional particles form a continuous convex structure on the surface of the fiber matrix.

[0158] A water-free fabric made of the water-free fiber is a plain fabric with a warp density of 130 strands / 10cm, a weft density of 150 strands / 10cm, and a gram weight of 300g / m 2 ;

[0159] The glossiness of the water-free fabric when the moisture content is 100wt% is 98.5% of the glossiness when the moisture content is 0wt%; the air permeability of the water-free fabric is 20mm / s; the water absorption rate of the water-free fabric is 155%, the water droplet diffusion time is 1.8s, the wicking height is 116mm, and the drying rate is 0.5g / h.

[0160] Example 5

[0161] A method for preparing water-free fiber, the specific steps are as follows:

[0162] (1) Raw material preparation:

[0163] PET: The manufacturer is Yizheng Chemical Fiber, the brand is FC510A;

[0164] Nano-TiO2;

[0165] Silane coupling agent: γ-methacryloxypropyltrimethoxysilane;

[0166] Catalyst: AlCl3;

[0167] MMA;

[0168] Initiator: dibenzoyl peroxide;

[0169] Chain transfer agent: dodecyl mercaptan;

[0170] HTEMPO (4-hydroxy-2,2,6,6-tetramethoxypiperidine, CAS: 2403-88-5);

[0171] (2) Preparation of functional particles:

[0172] (2.1) Add silane coupling agent and nano-TiO2 into a high-speed mixer, control the speed to 3000r / min, the temperature to 70℃, and stir for 2.8h;

[0173] (2.2) Add MMA and initiator to the reactor to react to obtain MMA prepolymer, then continue to add catalyst, chain transfer agent and the product of step (2.1) to the reactor to continue the reaction, then continue to add HTEMPO to the reactor to continue the reaction, after the reaction is completed, remove the small molecules in vacuo (i.e., at 190°C, reduce the pressure in the reactor to 75 Pa and maintain it for 15 minutes), and cool the discharged material;

[0174] Wherein, in steps (2.1) to (2.2), the mass ratio of silane coupling agent, nano-TiO2, MMA, initiator, chain transfer agent, catalyst, and HTEMPO is 1.5:60:35:0.01:0.5:0.01:2.98; in step (2.2), the temperature of the first reaction is 60°C, the pressure is 0.18MPa, the time is 1.5h, and the speed is 150r / min; the temperature of the second reaction is 85°C, the pressure is 0.4MPa, and the time is 1h; the temperature and pressure of the third reaction are the same as those of the second reaction, and the time is 1h;

[0175] (2.3) crushing the product of step (2.2) (pre-crushing, airflow crushing) to obtain functional particles with a D50 particle size of 280 nm;

[0176] (3) Preparation of water-free fibers:

[0177] (3.1) Blending the functional particles and PET to obtain a masterbatch;

[0178] Among them, the content of functional particles in the masterbatch is 58wt%;

[0179] (3.2) The masterbatch and PET are melt-spun to obtain fibers, and the obtained fibers are water-free fibers;

[0180] The process parameters of melt spinning include: the temperature of the screw extruder is 280°C for zone 1, 285°C for zone 2, 285°C for zone 3, 295°C for zone 4, and 295°C for zone 5; three pairs of drafting rollers are used in the melt spinning process, the temperature of the first pair of drafting rollers is 115°C and the rotation speed is 625m / min, the temperature of the second pair of drafting rollers is 128°C and the rotation speed is 2500m / min, and the temperature of the third pair of rollers is 220°C and the rotation speed is 3500m / min.

[0181] The final water-free fiber includes functional particles and a PET fiber matrix, with a specification of 100D / 96F and a tensile breaking strength of 6.03cN / dtex. The content of functional particles in the fiber is 12wt%. The functional particles are nano-TiO2 with an organic coating layer with a thickness of 18nm and a refractive index of 1.45 on the surface, and the organic coating layer is PMMA with a number average molecular weight of 3000g / mol. The functional particles form a continuous convex structure on the surface of the fiber matrix.

[0182] A water-free fabric made of the water-free fiber is a twill fabric with a warp density of 120 strands / 10cm, a weft density of 120 strands / 10cm, and a gram weight of 40g / m 2 ;

[0183] The glossiness of the water-free fabric when the moisture content is 100wt% is 97.2% of the glossiness when the moisture content is 0wt%; the air permeability of the water-free fabric is 20mm / s; the water absorption rate of the water-free fabric is 162%, the water droplet diffusion time is 1.4s, the wicking height is 121mm, and the drying rate is 0.52g / h.

[0184] Example 6

[0185] A method for preparing water-free fiber, the specific steps are as follows:

[0186] (1) Raw material preparation:

[0187] PET: The manufacturer is Yizheng Chemical Fiber, brand number is TFW100;

[0188] Nano-TiO2;

[0189] Silane coupling agent: a mixture of γ-methacryloxypropyltrimethoxysilane and vinyltriethoxysilane in a mass ratio of 1:1;

[0190] Catalyst: AlCl3;

[0191] MMA;

[0192] Initiator: dibenzoyl peroxide;

[0193] Chain transfer agent: dodecyl mercaptan;

[0194] HTEMPO (4-hydroxy-2,2,6,6-tetramethoxypiperidine, CAS: 2403-88-5);

[0195] (2) Preparation of functional particles:

[0196] (2.1) Add silane coupling agent and nano-TiO2 into a high-speed mixer, control the speed to 2600r / min, the temperature to 80℃, and stir for 3h;

[0197] (2.2) Add MMA and initiator to the reactor to react to obtain MMA prepolymer, then continue to add catalyst, chain transfer agent and the product of step (2.1) to the reactor to continue the reaction, then continue to add HTEMPO to the reactor to continue the reaction, after the reaction is completed, remove the small molecules in vacuo (i.e., at 190°C, reduce the pressure in the reactor to 78 Pa and maintain it for 15 minutes), and cool the discharged material;

[0198] Wherein, in steps (2.1) to (2.2), the mass ratio of silane coupling agent, nano-TiO2, MMA, initiator, chain transfer agent, catalyst, and HTEMPO is 1.5:70:25:0.01:0.5:0.01:2.98; in step (2.2), the temperature of the first reaction is 40°C, the pressure is 0.1MPa, the time is 2h, and the speed is 100r / min; the temperature of the second reaction is 90°C, the pressure is 0.3MPa, and the time is 2h; the temperature and pressure of the third reaction are the same as those of the second reaction, and the time is 1h;

[0199] (2.3) crushing the product of step (2.2) (pre-crushing, airflow crushing) to obtain functional particles with a D50 particle size of 340 nm;

[0200] (3) Preparation of water-free fibers:

[0201] (3.1) Blending the functional particles and PET to obtain a masterbatch;

[0202] Among them, the content of functional particles in the masterbatch is 60wt%;

[0203] (3.2) The masterbatch and PET are melt-spun to obtain fibers, and the obtained fibers are water-free fibers;

[0204] The process parameters of melt spinning include: the temperature of the screw extruder is 285°C for zone 1, 290°C for zone 2, 290°C for zone 3, 295°C for zone 4, and 290°C for zone 5; three pairs of drafting rollers are used in the melt spinning process, the temperature of the first pair of drafting rollers is 110°C and the rotation speed is 650m / min, the temperature of the second pair of drafting rollers is 125°C and the rotation speed is 2550m / min, and the temperature of the third pair of rollers is 210°C and the rotation speed is 3600m / min.

[0205] The final water-free fiber includes functional particles and a PET fiber matrix, with a specification of 75D / 36F and a tensile breaking strength of 5.88 cN / dtex. The content of functional particles in the fiber is 15wt%. The functional particles are nano-TiO2 with an organic coating layer with a thickness of 10 nm and a refractive index of 1.4 on the surface. The organic coating layer is PMMA with a number average molecular weight of 2500 g / mol. The functional particles form a continuous convex structure on the surface of the fiber matrix.

[0206] A water-free fabric made of the water-free fiber is a twill fabric with a warp density of 190 strands / 10cm, a weft density of 150 strands / 10cm, and a gram weight of 300g / m 2 ;

[0207] The glossiness of the water-free fabric when the moisture content is 100wt% is 99.8% of the glossiness when the moisture content is 0wt%; the air permeability of the water-free fabric is 18mm / s; the water absorption rate of the water-free fabric is 165%, the water droplet diffusion time is 1.2s, the wicking height is 126mm, and the drying rate is 0.56g / h.

Claims

1. A method for preparing water-free fiber, characterized in that: First, the functional particles and PET are blended and granulated to obtain master batches, and then the master batches and PET are melt-spun to obtain fibers, and the obtained fibers are water-free fibers; Among them, the D50 particle size of the functional particles is 70~340nm, and the content of the functional particles in the water-free fiber is 8~15wt%; three pairs of drafting rollers are used in the melt spinning process, the temperature of the first pair of drafting rollers is 110~115℃, the rotation speed is 600~650m / min, the temperature of the second pair of drafting rollers is 125~130℃, the rotation speed is 2400~2600m / min, and the temperature of the third pair of rollers is 210~220℃, and the rotation speed is 3000~3600m / min; The water-free fiber includes a fiber matrix and functional particles; the fiber matrix is ​​PET; the functional particles are nano-TiO2 with an organic coating layer on the surface; the organic coating layer is PMMA with a number average molecular weight of 2000~3000g / mol, a thickness of 10~20nm, and a refractive index of 1.4~1.5; the functional particles form a continuous convex structure on the fiber surface of the fiber matrix.

2. The method for preparing a water-free fiber according to claim 1, characterized in that: The preparation steps of functional particles are as follows: (a) Physical coating modification of nano-TiO2 using silane coupling agent; (b) adding MMA and an initiator to a reactor to react to obtain an MMA prepolymer, then adding a catalyst, a chain transfer agent and the product of step (a) to the reactor to continue the reaction, then adding HTEMPO to the reactor to continue the reaction, and after the reaction is completed, removing the small molecules in vacuum, and cooling the discharged material; (c) crushing the product of step (b) to obtain functional particles.

3. The method for preparing a water-free fiber according to claim 2, characterized in that: The silane coupling agent is one or more of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and vinyltriethoxysilane; The initiator is dibenzoyl peroxide, the chain transfer agent is dodecyl mercaptan, and the catalyst is AlCl3; The mass ratio of silane coupling agent, nano-TiO2, MMA, initiator, chain transfer agent, catalyst and HTEMPO is 1~3:60~70:25~35:0.01~0.05:0.5~1:0.01~0.05:1~4.

4. The method for preparing a water-free fiber according to claim 2, characterized in that: The specific process of step (a) is as follows: adding silane coupling agent and nano-TiO2 into a high-speed mixer, controlling the speed to 2500-3000 r / min, the temperature to 70-80°C, and stirring for 2-3 hours; In step (b), the temperature of the first reaction is 40-60°C, the pressure is 0.1-0.2 MPa, the time is 1-2 h, and the speed is 100-150 r / min; the temperature of the second reaction is 60-90°C, the pressure is 0.2-0.4 MPa, and the time is 1-2 h; the temperature and pressure of the third reaction are the same as those of the second reaction, and the time is 0.5-1 h.

5. The method for preparing water-free fiber according to claim 1, characterized in that: The process parameters of melt spinning include: the temperature of the screw extruder is 280~285℃ for zone 1, 285~290℃ for zone 2, 285~290℃ for zone 3, 295~300℃ for zone 4, and 290~295℃ for zone 5.

6. The method for preparing water-free fiber according to claim 1, characterized in that: The specifications of water-free fibers are 20~300D / 24~576F, and the tensile breaking strength is 5.88~6.25cN / dtex.

7. A water-free fabric, characterized in that: The water-free fiber is woven from water-free fibers, and the water-free fibers are prepared by the preparation method of water-free fibers as described in any one of claims 1 to 6.

8. The water-traceless fabric according to claim 7, characterized in that: Water-free fabric is knitted fabric, the number of circular knitting needles is 40G, and the weight is 150~300g / m 2 Or, the water-free fabric is a plain fabric with a warp density of 120-130 strands / 10cm, a weft density of 130-150 strands / 10cm, and a gram weight of 40-300g / m 2 ; Alternatively, the water-free fabric is a twill fabric with a warp density of 120~190 strands / 10cm, a weft density of 120~150 strands / 10cm, and a gram weight of 40~300g / m 2 ; The percentage of glossiness of water-free fabrics when the moisture content is 100wt% to the glossiness when the moisture content is 0wt% is 95-100%; The air permeability of water-free fabric is 18~23mm / s; The water absorption rate of the water-free fabric is ≥152%, the water droplet diffusion time is ≤1.9s, the wicking height is ≥112mm, and the drying rate is ≥0.46g / h.

Citation Information

Patent Citations

  • Light-resistant and highly anti-transparent fiber and fabric

    CN113699610A

  • High-transparency composite fiber, fabric and preparation method of high-transparency composite fiber

    CN115044998A

  • Manufacturing method of polypropylene composite fiber waterproof fabric

    CN117210992A

  • Permeable, sweat-stain-resistant, quick-dry and anti-ultraviolet fabric and preparation method and application thereof

    CN117261377A

  • Anti-perspective PTT fiber and preparation method thereof

    CN104963014A

Cited By

  • Preparation method of water traceless high-performance polypropylene fiber

    CN122406398A